2021
DOI: 10.11646/zootaxa.4991.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Five new species of Western Atlantic stardrums, Stellifer (Perciformes: Sciaenidae) with a key to Atlantic Stellifer species

Abstract: Five new species of Stellifer are described from the Caribbean Sea and tropical southwestern Atlantic. Among the previously recognized stelliferine genera, Stellifer is unique by having a pair of variably developed appendages on the posterior margin of the anterior gas chamber, which is lacking in Bairdiella, Corvula, Elattarchus, Odontoscion and Ophioscion. However, recent genetic studies indicated that Stellifer and Ophioscion are not monophyletic. The genus Ophioscion Gill, 1863 is recognized herein as a ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
2
10
2
Order By: Relevance
“…Further, patterns of rostral pores are of importance when distinguishing the Umbrina spp. [17,18,20]. Overall, the morphology and the livery of the U. ronchus specimen caught in the Strait of Sicily were consistent with the description by Tortonese [16] and Chao and Trevanas [17].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Further, patterns of rostral pores are of importance when distinguishing the Umbrina spp. [17,18,20]. Overall, the morphology and the livery of the U. ronchus specimen caught in the Strait of Sicily were consistent with the description by Tortonese [16] and Chao and Trevanas [17].…”
Section: Discussionsupporting
confidence: 83%
“…[17,18,20]. Overall, the morphology and the livery of the U. ronchus specimen caught in the Strait of Sicily were consistent with the description by Tortonese [16] and Chao and Trevanas [17]. In particular, their livery appeared gray with golden reflections, with neither oblique brown stripes nor markings.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The species listed in the Table 1 were identified following Figueiredo & Menezes (1978, , Britski et al (1984), Allen (1985, Harrison (2002), Marceniuk (2005), Marceniuk & Menezes (2007), McBride et al (2010, Lucena & Soares (2016), Marceniuk et al (2017Marceniuk et al ( , 2019bMarceniuk et al ( , 2020, Chao et al (2021). The fish species nomenclature followed Fricke et al (2022) and the taxonomic order according to Nelson et al (2016), except for Triportheidae and Labridae.…”
Section: Fish Datamentioning
confidence: 99%
“…Phylogenetic analyses based on multilocus data have shown that Stellifer and Ophioscion are not monophyletic, as suggested previously, and thus require a detailed taxonomic review [ 7 , 9 , 10 ]. More recently, Chao et al [ 8 ] recognized Ophioscion as a junior synonym of Stellifer based on morphological analysis, which means that Stelliferinae is currently made up of only five genera ( Stellifer , Bairdiella , Odontoscion , Corvula , and Elattarchus ). Chao et al [ 8 ] also described five new Stellifer species– Stellifer cervigoni , Stellifer collettei , Stellifer musicki , Stellifer macallisteri , and Stellifer menezesi , the latter previously identified as lineage II of Ophioscion punctatissimus Meek and Hildebrand, 1925 by Silva et al [ 10 ].…”
Section: Introductionmentioning
confidence: 99%